Collective action: mistakes of interpretations - Araújo, Silvia Maria de (2006)
This article focuses on the collective action as a category of analysis and a controversial phenomenon in the contemporary society. It uses basis in the history and sociological theory, from concepts of social action, social class, and the nature of the tense report between individual and society.